KWL: Strategy on Improving Reading Comprehension - Cut Intan Maulida; Sofyan A. Gani (Research in English and Education Journal, 2016)
This study is about the implementation of Know, Want, Learned (KWL) strategy to enhance students’ reading comprehension. The desire to conduct the research toward this study is to investigate how the proper implementation of KWL helps the students’ increasing their ability in terms of reading skill. This study was approached quantitatively, specifically through an experimental method using the design of one group pretest-posttest. The population of this study was the first grade students at SMPN 3 Banda Aceh, while the sample of this study was VII-9 class which consisted of 30 students which was chosen randomly. The data for this study were obtained by using test as the instrument for collecting the data. Also, the data were analyzed using repeated measures T-test in order to prove the hypothesis. The calculation result showed that null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted, because the result of t-test calculated was 5.07, higher than t-table 2.04. Therefore, the writer concludes that teaching reading by using KWL gives good effect for students’ reading comprehension at SMPN 3 Banda Aceh.